Diffuse alveolar damage in a patient with rheumatoid arthritis under prolonged leflunomide treatment: A Case Report and Literature Review. Issue 26 (June 2016) - Keng, Li-Ta; Lin, Mong-Wei; Huang, Hsien-Neng; Chung, Kuei-Pin
Abstract : Abstract: Patients with rheumatoid arthritis (RA) often have pulmonary involvement, and interstitial lung disease (ILD) is the primary manifestation, in which diffuse alveolar damage (DAD) is a rare histopathologic pattern. Leflunomide (LEF) is a frequently prescribed disease-modifying antirheumatic drug for treating RA. LEF-related ILD in the form of DAD has been reported in patients with RA, with the duration of LEF treatment before symptom onset ranging from 6 to 1204 days. We present a case of elderly woman with RA under prolonged LEF treatment for >9 years (3291 days), who had acute respiratory failure with the initial presentation of exertional dyspnea, fever, chills, and productive cough for 2 days. The histopathologic result of surgical lung biopsy was compatible with DAD. She was diagnosed as having LEF-related ILD, based on correlated clinical history, compatible histopathologic examination and excluding possible infection after extensive survey. Although the causative role of LEF cannot be confirmed, this case still hints that LEF-related DAD may occur even if LEF has been prescribed for a prolonged period.